A Study on the Domestic Environmental Conditions and Its Impact on the Prevalent Morbidities - Shashwat S Nagar; Hirenkumar B Patel; Niraj Pandit (Medsci Publications, 2018)
Background: Man is responsible for the pollution of his environ- ment through urbanization, industrialization and other human ac- tivities. The success of any health policy or health care intervention depends upon a correct understanding of socio-economic, envi- ronmental and cultural factors which determine the occurrence of diseases and deaths. Objectives: the study was conducted to study the Environmental Conditions of the population residing in the given settings and al- so to study the impact of these environmental condition on the Morbidities prevailing in the Population. Methods: A community based cross sectional study was done in Sankheda Taluka of Chhotaudaipur district. A total of 250 families in the village including 1452 subjects were enrolled in the study. Results: The housing and environmental conditions were assessed and given scores and categorized as Good, Average and Poor. These scores were then associated with the presence of morbidities like Respiratory Disease ,Vector borne Disease, Skin Disease , Oph- thalmic Disease, Gastrointestinal Disease, ENT Disease and it was seen that they were significantly associated with prevailing envi- ronmental risk factors in the population. Conclusion: The housing and environmental conditions play a significant role and are associated with occurrence of diseases in- volving various systems, hence these conditions must be given due attention so that it shall significantly lower the disease burden in any community.